Laser‐induced lithotripsy: a review, insight into laboratory work, and lessons learned. Issue 1 (8th March 2020) - Strittmatter, Frank; Eisel, Maximilian; Brinkmann, Ralf; Cordes, Jens; Lange, Birgit; Sroka, Ronald
Abstract: This manuscript summarizes the laser‐induced method for the destruction of kidney stones. Special emphasis is placed on laser‐induced lithotripsy, and a historical overview is given from the early beginnings in 1968 to the current developments. New laser parameter settings have to be tested in order to characterize novel laser devices for best clinical results and to meet demanding medical needs. At present, the stones are usually dusted, which makes it possible to flush these tiny fragments out of the urinary system without having to remove larger fragments additionally. Two in vitro setups were used to quantitatively evaluate the dust content and stone movement (propulsion) in a defined laboratory environment. The autofluorescence of stones can be used either to verify a stone‐free environment or to introduce safety measures such as differentiation between stone and tissue. In addition to describing these state‐of‐the‐art methods, a historical overview is given from the early beginnings in 1968 to the current developments. Abstract : This study provides an overview of laser‐induced lithotripsy, the latest technological developments, scientific findings, and lessons learned. Special focus is placed on fragmentation efficiency and optimization of lithotripsy, as well as on fluorescence‐based feedback technologies, which play a further role in the development of laser‐induced lithotripsy.